Uraz perforujący gałki ocznej z pozostawieniem nieorganicznego ciała obcego w oczodole – opis przypadku - Woyna-Orlewicz, Anna; Wylęgała, Edward; Słoka, Adam; Teper, Sławomir; Piłat, Jarosław; Orska, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Authors would like to present a case of perforating eye injury with inorganic foreign body, which consequently stick behind the globe in muscular cone space. We discuss visual prognosis after injury which depends on injury mechanism, wound extension and localization as well as tolerance of intraorbital foreign body through eye`s tissue and prevention of eye injuries. We would like to stress the necessity of meticulous primary microsurgical repair and possible secondary surgical reparation to reduce posttraumatic visual loss. There is also a possibility of late complication due to vitreoretinal proliferation as a consequence of healing process.